A method for preparing ammonium heptamolybdate
By preparing a high specific gravity ammonium tetramolybdate solution and performing crystal reforming, long-term and high-activity ammonium heptamolybdate was prepared, solving the problem of its high water solubility limiting the activity and long-term effectiveness of the catalyst.
Patent Information
- Application Number
- CN202411880683.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The high water-soluble properties of ammonium heptamolybdate in the field of catalysts for petrochemicals limit the activity and long-term effectiveness of the catalyst, affecting the service life and catalytic performance of the catalyst.
By preparing a solution of ammonium tetramolybdate with a specific gravity of ≥1.5, crystals were obtained by crystallizing an unstable ammonium heptamolybdate crystal, and heated in a closed environment with a humidity greater than 95% to obtain long-term and highly active ammonium heptamolybdate.
This method improves the supersaturation of the solution, speeds up the crystal crystallization rate, increases the hydrophobic properties of ammonium heptamolybdate, extends the process processing time of the catalyst, and improves the long-term effectiveness and activity of the catalyst.
Smart Images

Figure CN119320171B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ammonium heptamolybdate preparation, and more specifically, to a method for preparing ammonium heptamolybdate. Background Art
[0002] Ammonium heptamolybdate, also known as ammonium paramolybdate, is a type of molybdate. It is usually a colorless or light green crystalline powder. It is soluble in water but insoluble in ethanol and acetone. Its relative density is 2.498g / cm³.
[0003] The existing preparation processes of ammonium heptamolybdate include cooling crystallization and ion exchange. Among them, the cooling crystallization method is to dissolve ammonium tetramolybdate in ammonia water, and crystallize the ammonium heptamolybdate by cooling. After the crystallization is completed, it is filtered by centrifugation to obtain the filter residue, and the filter residue is dried to obtain ammonium heptamolybdate; in the experiment, the density of the solution after the ammonium tetramolybdate is dissolved needs to be controlled at about 1.5g / cm³, the pH value of the solution is 6-7, and the temperature of the solution is controlled not to exceed 70°C. The ion exchange method is to leach molybdenum roasted sand with alkali solution to obtain a molybdate solution, and the molybdate solution flows through an ammonium type cationic resin. The impurity metals in the solution replace the ammonium ions and adsorb on the resin, while the molybdenum is MoO4 2- The ion exchanged solution is evaporated, concentrated and crystallized or cooled and crystallized to obtain ammonium heptamolybdate.
[0004] Ammonium heptamolybdate is widely used in the field of catalysts, especially in the production of catalysts for petrochemical industry. In the catalytic cracking and hydrogenation reaction of petroleum, ammonium heptamolybdate is used as the active component of the catalyst to promote the reaction and improve the yield and selectivity of the reaction.
[0005] However, in the field of petrochemical catalysts, the high water solubility of ammonium heptamolybdate will limit the activity and long-term effectiveness of the catalyst under certain working conditions, seriously affecting the service life of the catalyst, reducing the catalytic performance of the catalyst, and thus reducing production efficiency. How to solve this problem is something we need to think about. Summary of the invention
[0006] In order to further prepare ammonium heptamolybdate which is almost insoluble in water in a short period of time and has long-lasting and high activity, the present application provides a method for preparing ammonium heptamolybdate.
[0007] The present application provides a method for preparing ammonium heptamolybdate, which adopts the following technical solution:
[0008] In a first aspect, the present application provides a method for preparing ammonium heptamolybdate, comprising the following steps:
[0009] (1) preparing an ammonium tetramolybdate solution with a specific gravity ≥ 1.5, and then crystallizing to obtain unstable ammonium heptamolybdate crystals;
[0010] (2) The unstable ammonium heptamolybdate crystals are heated in a closed environment with a humidity greater than 95% to 95-105°C, and the temperature is maintained to reform the crystals to obtain ammonium heptamolybdate.
[0011] By adopting the above technical scheme, the specific gravity of the solution is increased, the supersaturation of the solution is improved, the crystallization rate of the crystals is accelerated, and the production efficiency is improved; the unstable ammonium heptamolybdate crystals are restructured to produce a hydrophobic structure on the surface of the crystals, which exhibits a short-term hydrophobic state in the aqueous solution, thereby extending the process processing time of the catalyst and making the catalyst have long-term effectiveness.
[0012] Preferably, in step (1), the ammonium tetramolybdate solution consists of ammonium tetramolybdate, aqueous ammonia and deionized water.
[0013] By adopting the above technical solution, ammonium ions can be combined with molybdate ions, so that the molybdate ions in ammonium tetramolybdate can be better dispersed in the solution, and a uniform and stable ammonium molybdate solution is prepared. During the crystallization process, the formation of crystal nuclei is accelerated, the growth rate of crystals is increased, the formation of unstable ammonium heptamolybdate crystals is promoted, the degree of crystal reorganization is increased, and the thickness of the hydrophobic layer on the surface of ammonium heptamolybdate is increased, thereby improving the hydrophobic performance.
[0014] Preferably, the preparation method of ammonium tetramolybdate comprises the following steps: uniformly mixing sodium molybdate, ammonium chloride and deionized water, and acid precipitation to obtain ammonium tetramolybdate.
[0015] By adopting the above technical scheme, sodium molybdate and ammonium chloride undergo double decomposition reaction in deionized water to form a uniform and stable ammonium molybdate solution, reduce the presence of impurities in tetramolybdic acid, improve the purity of ammonium tetramolybdate, and then improve the purity of unstable ammonium heptamolybdate, and then reduce the interference of impurities on the formation of discrete oxygen bridge bonds during the crystal reforming process, thereby improving the long-term and high-activity performance of ammonium heptamolybdate.
[0016] Preferably, the mass ratio of the sodium molybdate, ammonium chloride and deionized water is (2-2.1):(1-1.1):100.
[0017] By adopting the above technical scheme, in the process of preparing ammonium tetramolybdate, the occurrence of side reactions is reduced, ammonium tetramolybdate crystals with uniform particle size and regular crystal shape are formed, the solubility of ammonium tetramolybdate in aqueous ammonia solution is improved, and in the process of forming unstable ammonium heptamolybdate, the solution concentration is increased, the crystallization rate is increased, the formation of unstable ammonium heptamolybdate crystals is promoted, the degree of crystal reorganization is increased, and the hydrophobicity of ammonium heptamolybdate is improved.
[0018] Preferably, the process parameters of the acid precipitation are: temperature 55-65°C, pH value 2.3-2.5.
[0019] By adopting the above technical scheme, the crystallization and precipitation of ammonium tetramolybdate is promoted, and at the same time, the obtained ammonium tetramolybdate has a higher purity, better crystal morphology and particle size. During the ammonia dissolution process, the dissolution rate of ammonium tetramolybdate is relatively stable, which helps to accurately control the combination ratio of molybdate ions and ammonium ions, and the prepared ammonium heptamolybdate has a suitable molybdenum content.
[0020] Preferably, the molar ratio of ammonium tetramolybdate to aqueous ammonia is (0.65-0.75):1.
[0021] By adopting the above technical scheme, the formation of unstable ammonium heptamolybdate crystals of the target product is ensured, the occurrence of side reactions is reduced, the stability of the crystal reforming process is maintained, the activity of ammonium heptamolybdate is increased, and the surface of ammonium heptamolybdate has a better ordered uneven state, thereby increasing its hydrophobicity.
[0022] Preferably, the mass percentage concentration of the ammonia water is ≥20%.
[0023] By adopting the above technical scheme, the solute content of the ammonium tetramolybdate solution used to prepare unstable ammonium heptamolybdate is increased, the specific gravity of the ammonium tetramolybdate solution is improved, the crystallization rate is accelerated, the formation of unstable ammonium heptamolybdate crystals is promoted, and it is beneficial to crystal reorganize the unstable ammonium heptamolybdate crystals, so that the ammonium heptamolybdate has long-lasting and high-activity properties.
[0024] Preferably, in step (1), the pH value of the ammonium tetramolybdate solution is 6.3-6.7, and the temperature is ≥90°C.
[0025] By adopting the above technical scheme, the pH value of the ammonium tetramolybdate solution is controlled, the purity of the unstable ammonium heptamolybdate generated by crystallization is increased, and the influence of impurities on the activity of the ammonium heptamolybdate is avoided; different from the temperature of the ammonium tetramolybdate solution during the preparation of conventional stable ammonium heptamolybdate, the temperature of the ammonium tetramolybdate solution is increased, the supersaturation of the crystallization solution is increased, and the formation of unstable ammonium heptamolybdate is promoted. In the process of crystal reforming, ammonium ions are more likely to form new chemical bonds with MoO3, thereby improving the activity of the ammonium heptamolybdate.
[0026] Preferably, in step (1), the cooling rate of the crystallization process is 20-50°C / min.
[0027] By adopting the above technical solution, crystal formation is accelerated, crystallization time is shortened, and crystallization efficiency is increased. A large amount of crystal products can be obtained in a short time, and the crystal structure is in an irregular state, ensuring the generation of unstable ammonium heptamolybdate different from the conventional steady state, which is convenient for recrystallization. The surface of ammonium heptamolybdate is more likely to form an irregular structure, thereby increasing hydrophobicity.
[0028] In the second aspect, the present application provides an application field of ammonium heptamolybdate prepared by the above technical scheme, wherein the ammonium heptamolybdate is used in the field of petrochemical catalysts, and the preparation of the catalyst comprises the following steps: uniformly mixing titanium dioxide, ammonium heptamolybdate, and deionized water, drying, calcining, and tableting to obtain the catalyst.
[0029] In summary, this application has the following beneficial effects:
[0030] 1. The ammonium heptamolybdate prepared in the present application exhibits higher chemical activity due to the change in the molecular arrangement of the crystal surface during crystal reformation, and the ammonium ions on the surface are bonded to MoO3 with discrete oxygen bridge bonds. It is this particularity that exhibits special properties of long-term and high activity in some special catalysts prepared.
[0031] 2. During the crystal reorganization process, the surface ions of unstable ammonium heptamolybdate are recrystallized, the surface structure is reshaped, and a hydrophobic structure is generated on the crystal surface. When dissolved in water, a suspension is formed in the water, showing a short-term hydrophobic state. It can be dissolved under alkaline conditions or by extending the dissolution time.
[0032] 3. After the unstable ammonium heptamolybdate is crystallized, the particle size of the obtained ammonium heptamolybdate becomes smaller and the density is larger, ranging from 3.3-3.5g / cm 3 It is significantly higher than water-soluble ammonium heptamolybdate, harder and brittle, with a Mohs hardness between 2.5 and 3.0, which is harder than water-soluble ammonium heptamolybdate. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscope photograph of ammonium heptamolybdate prepared in Example 3 of the present application, with a magnification of 10,000.
[0034] Figure 2 This is a scanning electron microscope photograph of ammonium heptamolybdate prepared in Comparative Example 1 of the present application, with a magnification of 1000.
[0035] Figure 3 It is the crystal X-ray diffraction fitting spectrum of ammonium heptamolybdate prepared in Example 1 of the present application and ammonium heptamolybdate prepared in Comparative Example 1.
[0036] Figure 4 It is a schematic diagram of the catalytic performance of the catalysts prepared in Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION
[0037] The present application is further described in detail below with reference to the embodiments.
[0038] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0039] Example 1
[0040] The preparation of ammonium heptamolybdate of the present embodiment comprises the following steps:
[0041] (1) 2 g of sodium molybdate, 1 g of ammonium chloride and 100 g of deionized water were mixed evenly, stirred and heated to 55°C, and then nitric acid with a molar concentration of 5 mol / L was added to adjust the pH to 2.3. Crystal precipitation was observed. After crystallization was completed, high-speed centrifugation was performed to dehydrate, and solid-liquid separation was performed to retain the solid component to obtain ammonium tetramolybdate crystals;
[0042] (2) 40.82 g of ammonium tetramolybdate crystals and 9.2 mL of 20% ammonia water were mixed evenly, stirred and heated to 90°C, deionized water was added to adjust the pH to 6.3 and the specific gravity to 1.5 to obtain a mixed solution, the mixed solution was filtered, the filtrate was put into a crystallizer, cooled at a rate of 20°C / min, and crystallized. After the crystallization was completed, high-speed centrifugation was performed to dehydrate, and solid-liquid separation was performed to retain the solid component to obtain unstable ammonium heptamolybdate crystals;
[0043] (3) The unstable ammonium heptamolybdate crystals are placed in a fully sealed oven, the humidity in the fully sealed oven is controlled to be 95%, and the temperature is raised to 95° C. and kept at this temperature for 3 hours to obtain ammonium heptamolybdate.
[0044] The preparation method of the catalyst in this embodiment is as follows: take 60g of deionized water in a 150mL beaker, add 10g of ammonium heptamolybdate and stir to dissolve, then add 50g of titanium dioxide, stir at room temperature for 6h, then heat and stir to remove excess water in the beaker, take out the titanium dioxide, dry it at 120℃ for 6h, calcine it at 600℃ for 4h, and press the calcined titanium dioxide into tablets to obtain a catalyst.
[0045] Example 2
[0046] The preparation of ammonium heptamolybdate of the present embodiment comprises the following steps:
[0047] (1) 2.1 g of sodium molybdate, 1.1 g of ammonium chloride and 100 g of deionized water were mixed evenly, stirred and heated to 65°C, and then nitric acid with a molar concentration of 8 mol / L was added to adjust the pH to 2.5. Crystal precipitation was observed. After crystallization was completed, high-speed centrifugation was performed to dehydrate, and solid-liquid separation was performed to retain the solid component to obtain ammonium tetramolybdate crystals;
[0048] (2) 47.1 g of ammonium tetramolybdate crystals and 7.5 mL of 25% by mass ammonia water were mixed evenly, stirred and heated to 100°C, deionized water was added to adjust the pH to 6.7 and the specific gravity to 1.7 to obtain a mixed solution, the mixed solution was filtered, and the filtrate was put into a crystallizer, cooled at a rate of 50°C / min, and crystallized. After the crystallization was completed, high-speed centrifugation was performed for dehydration, and solid-liquid separation was performed to retain the solid component to obtain unstable ammonium heptamolybdate crystals;
[0049] (3) The unstable ammonium heptamolybdate crystals are placed in a fully sealed oven, the humidity in the fully sealed oven is controlled to 97%, the temperature is raised to 105° C., and the temperature is kept for 2 hours to obtain ammonium heptamolybdate.
[0050] The preparation method of the catalyst of this embodiment is as follows: take 70g of deionized water in a 150mL beaker, add 12g of ammonium heptamolybdate and stir to dissolve, then add 50g of titanium dioxide, stir at room temperature for 6h, then heat and stir to remove excess water in the beaker, take out the titanium dioxide, dry it at 120℃ for 6h, calcine it at 550℃ for 4h, and press the calcined titanium dioxide into tablets to obtain the catalyst.
[0051] Example 3
[0052] The preparation of ammonium heptamolybdate of the present embodiment comprises the following steps:
[0053] (1) 2.06 g of sodium molybdate, 1.07 g of ammonium chloride and 100 g of deionized water were mixed evenly, stirred and heated to 60°C, and then nitric acid with a molar concentration of 6 mol / L was added to adjust the pH to 2.4. Crystal precipitation was observed. After crystallization was completed, high-speed centrifugation was performed to dehydrate, and solid-liquid separation was performed to retain the solid component to obtain ammonium tetramolybdate crystals;
[0054] (2) 45 g of ammonium tetramolybdate crystals and 6.4 mL of 30% ammonia water were mixed evenly, stirred and heated to 105° C., deionized water was added to adjust the pH to 6.5 and the specific gravity to 1.8 to obtain a mixed solution, the mixed solution was filtered, and the filtrate was put into a crystallizer, cooled at a rate of 30° C. / min, and crystallized. After the crystallization was completed, high-speed centrifugation was performed to dehydrate, and solid-liquid separation was performed to retain the solid component to obtain unstable ammonium heptamolybdate crystals;
[0055] (3) The unstable ammonium heptamolybdate crystals are placed in a fully sealed oven, the humidity in the fully sealed oven is controlled to 96%, the temperature is raised to 100°C, and the temperature is kept for 2.2 hours to obtain ammonium heptamolybdate.
[0056] The preparation method of the catalyst in this embodiment is as follows: take 80g of deionized water in a 150mL beaker, add 15g of ammonium heptamolybdate and stir to dissolve, then add 60g of titanium dioxide, stir at room temperature for 7h, then heat and stir to remove excess water in the beaker, take out the titanium dioxide, dry it at 120℃ for 6h, calcine it at 600℃ for 4h, and press the calcined titanium dioxide into tablets to obtain the catalyst.
[0057] Comparative Example 1
[0058] The preparation method of ammonium heptamolybdate of this comparative example comprises the following steps:
[0059] Take 60g of ammonium tetramolybdate and 40g of deionized water and mix them, add 3.4mL of 25% ammonia water by mass and mix them evenly, filter the obtained solution, add the filtrate to a DTB type crystallizer, and crystallize by a water-cooled jacket. The stirring speed is controlled at 65-75r / min. When the crystallizer medium temperature is cooled to 20°C, the solution is centrifuged to obtain a crystal cake, and the cake is dried to obtain ammonium heptamolybdate.
[0060] The preparation method of the comparative example catalyst is as follows: take 80g of deionized water in a 150mL beaker, add 15g of ammonium heptamolybdate and stir to dissolve, then add 60g of titanium dioxide, stir at room temperature for 7h, then heat and stir to remove excess water in the beaker, take out the titanium dioxide, dry it at 120℃ for 6h, calcine it at 600℃ for 4h, and press the calcined titanium dioxide into tablets to obtain a catalyst.
[0061] Performance testing
[0062] 1. Determination of Mo content
[0063] Referring to standard YS / T555.1-2009, after the sample is placed in a beaker, it is dissolved in a saturated solution of nitric acid-potassium chlorate.
[0064] 2. Determination of water solubility and water-soluble clarity
[0065] At 25°C, place the sample in a 250mL beaker, add 100mL of deionized water, stir magnetically for 20min, let stand, and observe the state of the solution.
[0066] 3. Catalyst performance test
[0067] The catalyst was placed in the middle section of a tubular furnace and reduced under a hydrogen atmosphere. The tubular furnace was purged with nitrogen during the heating and cooling process. The ammonia introduction rate was 150 mL / min, and the heating rate was 5°C / min. After the temperature reached 400°C, the gas flow in the tubular furnace was switched to hydrogen, and the introduction rate remained unchanged. The reduction was carried out for 1.5 hours. After the reduction was completed, it was switched to nitrogen for cooling. 1.5 g of the catalyst cooled to room temperature was filled into the constant temperature zone in the middle section of the fixed bed. The fixed bed was filled with inert porcelain balls above and below, and nitrogen was introduced at a rate of 200 mL / min. The temperature was raised to 350°C, and then the nitrogen was switched to hydrogen at a rate of 200 mL / min. Then, feeding was started. A 0.1% mass percent concentration of 2-cyclopentene-1-one in n-hexane was pumped into the reactor through a liquid feed pump at a flow rate of 0.2 mL / min. The performance test data of the catalysts prepared in Examples 1-3 and Comparative Example 1 are shown in Table 2, and the schematic diagram of the catalytic performance is shown in Figure 4 shown.
[0068] 4. The morphology of the ammonium heptamolybdate of Example 3 and the ammonium heptamolybdate of Comparative Example 1 was observed using a scanning electron microscope to obtain scanning electron microscope photos, as shown in FIG. Figure 1 and Figure 2 shown.
[0069] 5. X-ray diffraction test was performed on the ammonium heptamolybdate of Example 1 and the ammonium heptamolybdate of Comparative Example 1 using an X-ray diffractometer to obtain a crystal X-ray diffraction fitting spectrum, as shown in FIG. Figure 3 shown.
[0070] The performance test data of Example 1, Example 2, Example 3 and Comparative Example 1 are shown in Table 1 below:
[0071] Table 1 Data test
[0072]
[0073] The performance test data of the catalyst prepared in Example 3 and the catalyst prepared in Comparative Example 1 are shown in Table 2 below:
[0074] Table 2 Catalyst performance test data
[0075]
[0076] By analyzing Examples 1-3 and Comparative Example 1 and combining with Tables 1-2, it can be seen that the ammonium heptamolybdate treated with crystal reforming is suspended in water. By increasing the dissolution time, the ammonium heptamolybdate treated with crystal reforming can be dissolved in water and present a clear state. In addition, the ammonium heptamolybdate treated with crystal reforming has the advantages of long-term effectiveness and high activity in the field of petrochemical catalysts.
[0077] It can be seen from Table 1 that when the ammonium heptamolybdate prepared in Examples 1-3 is dissolved in water, the solution is in a suspended state in a short time, during which the ammonium heptamolybdate is almost insoluble in water. As the dissolution time increases, the solution becomes clear. After the dissolution time is extended, the solubility of the ammonium heptamolybdate prepared in Examples 1-3 in water can reach 40 g / 100 mL.
[0078] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing ammonium heptamolybdate, characterized in that: The steps include: (1) using ammonium tetramolybdate, ammonia water and deionized water to prepare an ammonium tetramolybdate solution with a pH value of 6.3-6.7, a temperature ≥90°C and a specific gravity ≥1.5, and then cooling and crystallizing at a rate of 20-50°C / min to obtain unstable ammonium heptamolybdate crystals; (2) The unstable ammonium heptamolybdate crystals are heated in a closed environment with a relative humidity greater than 95% to 95-105°C, and kept at this temperature for 2 h, 2.2 h or 3 h to reform the crystals to obtain ammonium heptamolybdate.
2. A method for preparing ammonium heptamolybdate according to claim 1, characterized in that: The preparation method of ammonium tetramolybdate comprises the following steps: uniformly mixing sodium molybdate, ammonium chloride and deionized water, and performing acid precipitation to obtain ammonium tetramolybdate.
3. A method for preparing ammonium heptamolybdate according to claim 2, characterized in that: The mass ratio of the sodium molybdate, ammonium chloride and deionized water is (2-2.1):(1-1.1):
100.
4. A method for preparing ammonium heptamolybdate according to claim 2, characterized in that: The process parameters of the acid precipitation are: temperature 55-65° C., pH value 2.3-2.
5.
5. The method for preparing ammonium heptamolybdate according to claim 1, characterized in that: The mass percentage concentration of the ammonia water is 20%-30%.
Citation Information
Patent Citations
Staged cooling crystallization preparation method of ammonium heptamolybdate
CN118598189A